2023
DOI: 10.3389/fcell.2023.1083175
|View full text |Cite
|
Sign up to set email alerts
|

3D multicellular systems in disease modelling: From organoids to organ-on-chip

Abstract: Cell-cell interactions underlay organ formation and function during homeostasis. Changes in communication between cells and their surrounding microenvironment are a feature of numerous human diseases, including metabolic disease and neurological disorders. In the past decade, cross-disciplinary research has been conducted to engineer novel synthetic multicellular organ systems in 3D, including organoids, assembloids, and organ-on-chip models. These model systems, composed of distinct cell types, satisfy the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 154 publications
0
5
0
Order By: Relevance
“…The proof of concept of this has been shown, for example, in studies in which intestinal epithelial cells originally cultured as organoids were seeded in a microphysiological device recapitulating the structure of the small intestine provided the basis for differentiation into even rare cell types ( Nikolaev et al., 2020 ). The aggregation of organoids representing different tissues—assembloids—is also enabling much more complex human models ( Goldrick et al., 2023 ; Miura et al., 2022 ). The generation of combination tissue models in which TSC- and PSC-derived cells are combined is also an evolving area of activity.…”
Section: Some Final Words Of Caution For the Fieldmentioning
confidence: 99%
“…The proof of concept of this has been shown, for example, in studies in which intestinal epithelial cells originally cultured as organoids were seeded in a microphysiological device recapitulating the structure of the small intestine provided the basis for differentiation into even rare cell types ( Nikolaev et al., 2020 ). The aggregation of organoids representing different tissues—assembloids—is also enabling much more complex human models ( Goldrick et al., 2023 ; Miura et al., 2022 ). The generation of combination tissue models in which TSC- and PSC-derived cells are combined is also an evolving area of activity.…”
Section: Some Final Words Of Caution For the Fieldmentioning
confidence: 99%
“…The cell sources of intestinal organoids include ISCs from intestinal crypts, PSCs, embryonic SCs (ESCs), and iPSCs [ 18 , 56 ]. In 2009, Hans et al reported for the first time in Nature the formation of murine intestinal organoids with intestinal epithelial crypt structure using Lgr5(+) ISCs from mouse intestinal crypt in vitro [ 6 ].…”
Section: Ibd Intestinal Modelmentioning
confidence: 99%
“…[ 24 ] Contrarily to spheroids that are usually free‐floating, organoids are often maintained within an ECM structure that offers mechanical support to the cells. [ 25 ] Thanks to these characteristics, organoids can be exploited as an effective platform not only to evaluate drug response and efficiency, but also to develop personalized medicine approaches [ 26 ] or study brain aging phenomena in vitro. [ 27 ] A variety of NDD models have been developed using spheroid or organoid technologies and were able to secure accurate regulation over cell positioning and ECM material composition.…”
Section: Introductionmentioning
confidence: 99%
“…Despite all these advantages, they are still at an embryonic phase and massive efforts need to be directed toward the optimization of organoid generation. In fact, to achieve these goals, several limitations have to be overcome, [ 25 , 26 , 27 , 28 ] including: i) lack of standardization of complex protocols; ii) definition of growth factors and metabolites necessary to prolong the lifespan and self‐renewal of the organoids; iii) high costs and time consumption; iv) lack of vascularization, oxygen, and nutrient diffusion in the center of the organoid; and v) difficulties in replicating age‐related diseases.…”
Section: Introductionmentioning
confidence: 99%